Feasibility Study of Housing Project Development and Design in Baleendah District, Bandung - Saputri, Rifa Aqila; Chumaidiyah, Endang; Aryani, Sinta (JTI: Jurnal Teknik Industri, 2024)
The rapid pace of urbanization has heightened the demand for housing, making the housing industry increasingly significant. PT Fajar Ratna Kumala, a real estate company, plans to revive the XYZ Housing Project in Baleendah District in 2024, initially designed in 2014 but delayed due to internal issues. With a growing population, the company aims to develop the project on a 12-hectare rice field they acquired, necessitating a comprehensive feasibility evaluation to ensure market alignment and regulatory compliance. The feasibility analysis encompasses five main aspects: market, legal, environmental, technical, and financial, including sensitivity levels. The process involves data collection through primary (observations and interviews) and secondary (statistical data, literature, and historical data) methods, followed by data processing for all aspects. Market analysis forecasts an increasing housing demand from 2024 to 2028, guiding the planning of housing types and land use. Legal focuses on obtaining necessary permits and proofs to avoid legal complications. The environmental aspect estimates costs for environmental impact assessments (AMDAL) and evaluates potential environmental impacts. Technical planning includes 14 technical designs, while financial evaluation, using net present value (NPV), payback period (PBP), and internal rate of return (IRR), reveals an NPV of IDR 36,808,001,153.00, a PBP of 2.08 years, and an IRR of 64.17%, confirming the project's financial viability. Sensitivity analysis indicates the project is sensitive to cost and price fluctuations but remains within acceptable limits. This study provides PT Fajar Ratna Kumala with critical insights for project development and offers a valuable evaluation framework for future business feasibility assessments. Keywords: Feasibility, NPV, PBP, IRR, Sensitivity